Gamma-Irradiated Sterile Cornea for Use in Corneal Transplants in a Rabbit Model - Yoshida, Junko (Middle East Afr J Ophthalmol, 2015)
PURPOSE: Gamma irradiated corneas in which the donor keratocytes and endothelial cells are eliminated are effective as corneal lamellar and glaucoma patch grafts. In addition, gamma irradiation causes collagen cross inking, which stiffens collagen fibrils. This study evaluated gamma irradiated corneas for use in corneal transplantations in a rabbit model comparing graft clarity, corneal neovascularization, and edema. METHODS: Penetrating keratoplasty was performed on rabbits using four types of corneal grafts: Fresh cornea with endothelium, gamma irradiated cornea, cryopreserved cornea, and fresh cornea without endothelium. Slit lamp examination was performed at postoperative week (POW) one, two, and four. Corneal clarity, edema, and vascularization were graded. Confocal microscopy and histopathological evaluation were performed. A P < 0.05 was statistically significant. RESULTS: For all postoperative examinations, the corneal clarity and edema were statistically significantly better in eyes that received fresh cornea with endothelium compared to the other three groups (P < 0.05). At POW 1, gamma irradiated cornea scored better than the cryopreserved and fresh cornea without endothelium groups in clarity (0.9 vs. 1.5 and 2.6, respectively), and edema (0.6 vs. 0.8 and 2.0, respectively). The gamma irradiated corneas, cryopreserved corneas and the fresh corneas without endothelium, developed haze and edema after POW 2. Gamma irradiated cornea remained statistically significantly clearer than cryopreserved and fresh cornea without endothelium during the observation period (P < 0.05). Histopathology indicated an absence of keratocytes in gamma irradiated cornea. CONCLUSION: Gamma irradiated corneas remained clearer and thinner than the cryopreserved cornea and fresh cornea without endothelium. However, this outcome is transient. Gamma irradiated corneas are useful for lamellar and patch grafts, but cannot be used for penetrating keratoplasty.